Evaluating a Positive Allosteric Modulator Radiotracer Candidate to Image the Dopamine D1 Receptor - Verma, Megan (Université d'Ottawa | University of Ottawa, 2025)
The dopamine D1 receptor (D1R) is the most populous dopaminergic G-protein coupled receptor, triggering functional responses associated with cognition and movement. Although receptor abnormalities correlate with prevalent neurological conditions like Parkinson’s disease and schizophrenia, the relationship between D1R distribution and systemic dopaminergic outcomes requires further elucidation. D1R antagonists have been radiolabelled for PET imaging, but they show suboptimal target selectivity. However, positive allosteric modulators (PAMs) display non-orthosteric binding, theoretically reducing off-target signals. Among such compounds, ASP4345 was examined in preliminary clinical trials and showed activity at rodent and human receptors. Thus, we aim to evaluate ASP4345 as a positive allosteric modulator D1R radiotracer candidate. We synthesized ASP4345 over five steps and assessed molecular identity via NMR and mass spectrometry, achieving an overall yield of 86% in the final coupling step. Functional allostery was analyzed using dopamine and MLS1082, a known D1R PAM, in cAMP accumulation assays. In tandem, these experiments explored target selectivity by expressing the homologous dopamine D5 receptor (D5R). Subsequent analyses implied that ASP4345 binds to both D1-class receptors and exhibits a combined agonist-PAM profile.  Our next steps include identifying a radiolabeling precursor and analyzing in vivo binding in rodents through radiosynthetic screening and biodistribution experiments, respectively. Overall, these approaches will develop a PAM radiotracer workflow to study the dopaminergic system and eventually neurological disease.
Keywords: dopamine D1 receptor; dopamine; positive allosteric modulator; radiotracer development; pharmacology; positron emission tomography; G-protein coupled receptor; neuroscience